Optimal inventory control for ameliorating, deteriorating items under time varying demand condition (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In this paper we discuss the development of an inventory model for ameliorating items such as fast growing animals like duck, pigs, broiler  in poultry farm, high-bred fishes with instantaneous replenishment  for the above type of items under cost minimization. A time varying type of demand rate with infinite time horizon, constant deterioration and without shortage is considered for the model. The result is illustrated with numerical example.